The Importance of Getting to Know the Schools of Fiqh for Muslims in Indonesia - Heni Ani Nuraeni; Yusi Rida Alsyaina; Zulfa Salma Octavia (al-Afkar, Journal For Islamic Studies, 2024)
Madzhab is currently divided into 4, namely Hanafi, Maliki, Syafi'i, and Hanbali. The majority of Indonesian citizens adhere to the Imam Syafi'i school of thought, because Islam came through Middle Eastern Muslim traders, so these traders were the ones who spread the Syafi'i school of thought to Indonesian citizens. In writing this article the research method used is a qualitative research method with a bibliographic type. (library research), namely a method of collecting data by reading, understanding, and studying theories in various literature related to the discussion in this article. Collecting data by reading and searching for sources from several existing journals, books, and articles. The following is an explanation of the causes of differences in methods of implementing law enforcement among Imam Mujtahids, as a conclusion of various divisions according to the opinions of the figures. This can be summarized in general as follows: first: Differences in sources of law, second: Differences in how to understand texts, third: Differences in some of the linguistic conventions for understanding texts. Schools are natural and historical opinions. Madhab is Imam Mujtahid's opinion about the law of an event based on the Al-Qur'an and Hadith. The aims and benefits of studying schools of thought that impact the theological and political context of the development of jurisprudence as well as political events in the second to third centuries of the Hijriyah influenced each other.